Catechol versus carboxyl linkage impact on DSSC performance of synthetic pyranoflavylium salts. (November 2019) - Pinto, Ana Lucia; Cruz, Luis; Gomes, Vânia; Cruz, Hugo; Calogero, Giuseppe; de Freitas, Victor; Pina, Fernando; Parola, A. Jorge; Carlos Lima, J.
Abstract: Anthocyanins are the main polyphenolic dyes found in young red wines, which are transformed into more stable structures such as pyranoanthocyanins, during wine ageing and maturation. While anthocyanins practically lose their red color between pH 1 and 5, as a result of the formation of colorless hemiketals, pyranoanthocyanins practically do not change their color intensity. For that they constitute a photosensitizer family with great potential for bio-inspired dye-sensitized solar cells (DSSCs). In this work, a series of pyranoanthocyanin derivatives were designed, synthesized and applied for the first time as dye sensitizers in DSSCs. A relation was established between dye structure and cell efficiency. Specifically, the influence of different linker units, carboxyl and catechol, was studied in terms of their influence in the various parameters related to DSSC efficiency. The presence of the catechol unit was shown to be essential for efficient electron injection of the dye into the TiO2 semiconductor, since carboxylic units showed a deleterious effect in electron injection due to their electron withdrawing character. An overall efficiency of 1.15% was obtained for the best performing compound, 10-catecholpyrano-3′, 4', 5, 7-tetrahydroxyflavylium, with no further optimization. Highlights: For the first time pyranoflavylium salts were successfully applied as light harvesters in DSSCs. An overall efficiency of 1.15% was obtained with no further optimization. Catechol anchoring groups increase electron injection to the TiO2 semiconductor. Carboxylic anchoring groups showed deleterious effect in electron injection.